Gaya Kepemimpinan Organisasi pada Persekutuan Mahasiswa Kristen (PMK) di STTI-STIENI Jakarta - gary yefta herbeth siagian (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2020)
One very important factor for a leader in leading an organization in order to achieve a goal is the leadership style. Leadership style has a very close relationship of an organization. A good leadership style will produce an optimum performance. Performance is the overall result of a person in carrying out tasks during a certain period. The purpose of this study is to determine the leadership style, and the level of organizational leadership performance of the Christian Student Association (PMK) of the Indonesian National College of Technology and Economics Jakarta. Population of all students of the Indonesian College of Technology and Economics Jakarta. The sample used was 39 respondents. This research uses survey method. The method used is quota sampling. The analytical tool used is descriptive analysis and statistical analysis mode. The results of the study showed that the leadership style of the Christian Student Association of the Indonesian National College of Technology and Jakarta Jakarta found that the most dominant leadership style was the visionary leadership style of 3,11. While the leadership performance of the Christian student association organization of the Indonesian National College of Technology and Economics Jakarta showed sufficient results of 2,74. This research is expected to provide additional information and can be taken into consideration regarding the level of satisfaction of the organizational style of the Christian Student Association of Indonesian National Institute of Technology and Economics Jakarta.